80-lecie fenyloketonurii. Część II: pierwszy literacki oraz inne niemedyczne opisy choroby - Hozyasz, Kamil K.; Hozyasz, Julia L. (Pediatria Polska - Polish Journal of Paediatrics, 2017)
This review gives some insight into the descriptions of phenylketonuria in fiction literature (e.g. T. Storm’s The rider on the white horse, P.S. Buck’s The good earth) and biographies (e.g. P.S. Buck’s The child who never grew, Cj. Stevens’s The miracle of Bryan Pearce). The Storm’s novel was published in German in the year 1888, in which I.A. Følling, the discoverer of phenylketonuria, was born. Sources for the inspiration of the author of “The rider on the white horse’ are discussed. The study of patients’ descriptions in great works of fiction can stimulate medical professionals to recognize the psychological and sociological complexity and diversity of human life and the power and implications of what they do. It was suggested that the use of selected novels in medical education can provide an enriching humanistic balance which is often lacking in a strict textbook approach.